Analisis Perbandingan Usahatani Cabai Rawit Dan Tomat Dengan Pendekatan Resiko Investasi di Desa Tolite Jaya Kecamatan Tolinggula Kabupaten Gorontalo Utara - Amir Halid; Amelia Murtisari; Ilin Abuya (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
The objective research is to know which business farmer is more benefit and have more risk invest at Tolite Jaya village Tolinggula district Gorontalo Utara regency. Do on may-July 2013. The research design is using survey method consist primer data by interview chili and tomato farmer is using questionnaire and secondary data get from Tolite Jaya village work and BPS. The sample using surfeited sample where, the all population are sample. Data analysis is R/C and deviation standard analysis. Result analysis indicated the reception of chilly is Rp.58.986.000, with R/C Ration 3, 6 values. Based on decision criteria R/C Ratio values is more than one, it give benefits and can be afford and have more infestation risk 1,949. While tomato the reception is Rp. 7.575.600, with value R/C Ratio 0,8, it based on risk criteria is smaller and harm also have smaller infestation risk 1,113